Faktor-Faktor Yang Berhubungan Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Sigambal Tahun 2024 - Meirindany, Tina; Rahma Siregar, Nurul; Fithriani, Fithriani (Universitas Haji Sumatera Utara, 2024)
Pulmonary TB is the first highest level of disease in North Sumatra Province after malaria with 15,730 cases. This research method is a quantitative study with a cross sectional design located at Puskesmas Sigambal Labuhanbatu Regency. Sampling with accidental sampling technique totalling 50 people. Data analysis was carried out univariate in the frequency distribution table and bivariate analysis in the cross table using the Chi-Square test. The results showed that there was a relationship between knowledge, occupancy density, household contact history, smoking habits and disease history with the incidence of pulmonary TB in the Sigambal Health Centre Area, Labuhan Batu Regency. It is recommended that all family members should undergo TB screening to detect early and prevent transmission